2019
DOI: 10.1186/s12889-019-6831-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the alcohol drinking behavior and influencing factors among emerging adults and young adults: a cross-sectional study in Wuhan, China

Abstract: Background The relationship between alcohol use in adolescents and young adults and outcomes has not been widely researched in China. The aim of the current study was to understand the current status of drinking behavior of Chinese youth transitioning into adulthood. Methods The cross-sectional study included 1634 participants between 18 and 34 years of age. The participants were randomly chosen from 13 administrative districts in Wuhan, and invited to complete a questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
1
29
0
1
Order By: Relevance
“…In our analysis, we found that former drinkers were at a higher risk than current drinkers, which may mainly re ect the fact that former drinkers are routinely encouraged to quit drinking because of poor health. Indeed, studies have suggested that many people perceive alcohol use as harmless and only consider quitting drinking when they encounter health problems [18,19]. We also found a positive association between current drinking and cancer, especially in the case of heavy alcohol consumption.…”
Section: Discussionsupporting
confidence: 68%
“…In our analysis, we found that former drinkers were at a higher risk than current drinkers, which may mainly re ect the fact that former drinkers are routinely encouraged to quit drinking because of poor health. Indeed, studies have suggested that many people perceive alcohol use as harmless and only consider quitting drinking when they encounter health problems [18,19]. We also found a positive association between current drinking and cancer, especially in the case of heavy alcohol consumption.…”
Section: Discussionsupporting
confidence: 68%
“…Alcohol consumption has a complex association with health and is the leading risk factor for premature death and disability 25-27 . The prevalence of alcohol drinking was 13.52% in this study, consistent with findings in the survey of China Kadoorie Biobank (CKB) 24 , and the Wuhan study in 2015 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol consumption has a complex association with health and is the leading risk factor for premature death and disability 25-27 . The prevalence of alcohol drinking was 13.52% in this study, consistent with findings in the survey of China Kadoorie Biobank (CKB) 24 , and the Wuhan study in 2015 25 . Despite the fact that the prevalence of drinking in China is lower than in many Western and African populations 2,26,27 , the potential public health challenge induced by alcohol drinking should not be ignored by the Chinese Central Government (CCG).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A national representative study showed that 34.3% of participants in China described themselves as regular drinkers (54.6% for males and 13.3% for females) [8], and those who drank more also smoked more cigarettes [9]. In addition, a very recent study found that the prevalence of alcohol consumption was 45.84% for young Chinese people (drinkers' referred to those who have either drunk more than half a cup of alcohol at least once in the past 12 months or those who have drunk any quantity of alcohol at least twice in the past 12 months), suggesting an increase in alcohol use among young people [10].…”
Section: Introductionmentioning
confidence: 99%